High altitude and its effects on exercise performance - Graetzer, D.
Physical exercise at high elevations following rapid travel from sea level to the mountains has become common with the luxuries of modern travel. Running the Colorado Pike's Peak marathon (elevation 14,110 feet), rock climbing or backcountry skiing on Wyoming's Grand Tetons (elevation 13,770 feet), and alpine skiing or snowshoe hiking at Utah's Snowbird ski resort (elevation 11,000 feet) are familiar examples of high altitude sports. Does a rapid ascension to elevations of these magnitudes have a restrictive effect on athletic performance? Absolutely! The increased stress of altitude on the physiology of exercise began to be scientifically investigated following the 1968 Olympic Games in Mexico City (elevation 7,546 feet). For the first time in history, no world records were established in events lasting longer than 2.5 minutes while African runners who trained regularly at high altitudes dominated the endurance events. Subsequently, several Olympic, professional, and collegiate teams are now taking altitude adjustments into consideration during their training prior to competition. For example, prior to the 1988 NFL American conference championship football game in Denver's mile high stadium (elevation 5,280 feet), the Cleveland Browns practiced for one week at the University of New Mexico (elevation 5,314 feet). Altitude training for 7 days was not quite enough, however, as the Browns ran out of gas in the final minutes and the Broncos won 38 to 33. The human body requires a continuous supply of oxygen to the tissues to maintain the process of metabolism (the use of substrate for energy to maintain life-sustaining biological processes). The source of this oxygen is the ambient air where the percentage of oxygen remains fixed at 20.93% regardless of altitude. Ascent to a higher altitude causes a reduction in barometric pressure which induces a corresponding decrease in the partial pressure of oxygen of the inhaled air. For example, with ascent from sea level to the top of the tram at Snowbird's 11,000 foot Hidden Peak, the average barometric pressure decreases from about 760 mm Hg to about 510 mm Hg. The reduces the partial pressure of the inspired air from about 149 mm Hg to about 97 mm Hg. Partial pressure of the inspired air after it has been inhaled into the lungs and is fully saturated with water vapor is calculated as barometric pressure minus 47 times the percentage of oxygen in the ambient air: (Snowbird PIO2 = ((510 - 47) x .2093) = 96.9 mm Hg. This oxygen enters the body through the lungs where it binds reversible with hemoglobin in the bloodstream for transport to the tissues. A reduced partial pressure of oxygen will impair the oxygenation of blood flowing through the lungs. A bloodstream with a reduced oxygen saturation will consequently deliver diminished oxygen supply to the working muscles. At the muscle tissue level, oxygen is released from the blood and enters the cells of the working muscles to sustain aerobic metabolism. The preferred fuel for exercise at altitude appears to be fat due to a dramatic decrease in carbohydrate metabolism. This complex shift in substrate utilization is not well understood but may be due to the fact that a reduced oxygen supply already causes a higher lactic acid level in the muscles and bloodstream and carbohydrate consumption must be curtailed. Lactate is only produced during carbohydrate (not fat) breakdown. The end result of these occurrences is reduced maximal aerobic power, diminished endurance capacity, and earlier muscular fatigue during your high altitude ski vacation. Fortunately, there are several complex, physiological, interactions that work to minimize the effects of a reduced oxygen delivery to the tissues. Many of these adaptations occur quite early after high altitude exposure and include shifts in pul monary ventilation, the cardiovascular system, and the cellular composition of the blood. Ventilation rate (total amount of air moving in and out of the lungs) is stimulated at high elevations by an increase in breath frequency. This serves to raise oxygen availability to the alveoli in the lungs (site of oxygen extraction from the pulmonary system into the bloodstream). Unfortunately, hyperventilation also blows off excess carbon dioxide from the body which has the potential to disrupt acid-base balance of the tissues and contribute to altitude sickness. Considerable body water is also lost with high ventilatory rates leading to a relative state of dehydration. Airplane flights to higher altitudes also strongly contribute to dehydration because the relative humidity of airplane cabins and mountainous regions are generally quite low. A low humidity environment continually draws precious moisture from the body which must be replaced by fluid consumption. Altitude also stimulates an increase in heart rate and cardiac output (total amount of blood pumped by the heart) to increase blood circulation by the muscles to unload oxygen and pick up carbon dioxide and back to the alveoli to reverse these exchanges. This serves to compensate for the blood's reduced oxygen saturation but also provides more stress to the heart which may effect persons predisposed to heart disease. The composition of the blood changes after about 2 weeks of altitude exposure by producing more red blood cells and hemoglobin (the iron-protein compound that transports oxygen). Bone marrow stimulation to increase hematocrit (percentage of red cells in the blood) in addition to an increase in plasma volume serves to increase total blood volume. The benefits of blood adaptation in the weeks following exposure includes reducing the cardiac output required for oxygen delivery during rest and submaximal exercise, increasing maximal oxygen transport during strenuous exertion, and providing a larger fluid reserve for sweating. Several studies investigating the effect of high and low altitude training on exercise performance have been conducted. Competitions conducted at laboratories such as the Olympic Train ing Center at Colorado Springs (elevation 6,500 feet) have concluded that exercise at altitude can be severely restricted fol lowing conditioning at sea level. Physical activities begin to be affected at about 4,500 feet (depending on fitness level of the participant) due to reductions in ventilatory and cardiac ef ficiency. Endurance (aerobic) events are effected by altitude much more than sprinting or weight training (anaerobic) events. Training acclimatization time needs to be longer as the altitude becomes higher. Training for 14 days at 6,500 feet and 28 days at 8,000 feet are currently the best recommendations. Altitude chamber studies have indicated that full acclimatization at 7,500 feet is possible after a continuous stay of 4 weeks while complete adaptation to the extreme altitude of 13,000 feet is possible after a continuous stay for 14 months. Athletes can generally maintain the same exercise intensity during training but they should increase their rest periods by decreasing the duration and increasing the frequency of their workouts. Training at altitude, however, is only beneficial prior to competitions conducted at altitude as competition at a lower altitude have shown no advantage to altitude training. The following guidelines are recommended for persons traveling to a high altitude for a week of skiing or other exercise activity: 1. The major variables that effect your body's reaction to high altitude exercise include rate of ascent, altitude attained, length of acclimatization, and intensity, duration, and mode of exercise. Although individual response will vary considerably, use common sense and curtain strenuous exercise the first day upon arrival. This is especially important if you doing an activity (skiing, rock climbing) that you do not normally do at sea level. Be particularly attentive to the signs of fatigue (rapid heart rate, shortness of breath, light-headedness, muscle soreness) and reduce activity appropriately. On the other hand, do not loaf around and sleep upon arrival because light activity speeds the adjustment process. 2. Be aware that ascension to a mountainous region often encompasses other stressors such as cold, wind chill, and possibly jet lag. The cumulative effects of several environmental stressors amplify the effects beyond the sum of them individually. 3. Sleeping problems are a common complaint following ascension to high altitudes. Taking a 10 minute sauna or whirlpool hot bath (now standard equipment at most ski resorts) immediately prior to turning in will increase the quality and quantity of your sleep. Many ski lodges will deliver a humidifier to your room upon request which will increase water content of the air and relieve dried out sinuses. Putting a dab of petroleum jelly on the tips of your nostrils and inhaling steam over a hot water sink may also bring some temporary sinus relief. 4.Acetazolamide (diamox) taken at a dosage of 250 mg 3 times a day is commonly prescribed to persons suffering from mountain sickness or pulmonary edema. Symptoms of acute mountain sickness in decreasing order of frequency include headache, insomnia, anorexia, nausea, vomiting, and dizziness. High altitude pulmonary edema (buildup of fluid in the lungs) begins with symptoms of extreme lethargy and may lead to coughing up pink sputum, fever, rapid heart rate, and cyanosis. These illness have life-threatening potential because they alter the pH of the body. Consult a physician immediately. 5. Ultraviolet radiation increases by about 5% for every 1,000 feet of elevation, corresponding to 55% more UV rays at the top of the 11,000 foot Snowbird summit as compared to sea level. Using sunscreen and wearing UV sensitive sunglasses/goggles to protect your skin and eyes is especially important due to UV reflection off the snow. 6. A low humidity environment will continually suck moisture from your body but you may not notice it due to evaporation before sweat can form. Consuming plenty of fluids (while avoiding alcohol) is thus very important. Monitor your body weight and drink enough water to regain lost weight (consuming one pint of fluid will replenish one pound of water weight loss). Diets consumed during vacations sometimes involve a nutritional shift to more fatty foods which will effect fluid retention and also energy level. 7. Persons who are moderately sensitive to monosodium glutamate at sea level may become hypersensitive at high altitudes. Simply staying away from Chinese food may prevent nausea and cramping and salvage the ski weekend you have been saving for all year. 8. Giving your body time to acclimatize is the key to strenuous exercise at altitude. If you ever attempt to climb Mount Everest (elevation 24,000 feet) or Mount McKinley (elevation 20,320 feet) begin your ascent at less than 10,000 feet if arriving by aircraft or motor vehicle and keep your daily ascent rate to less than 1,000 feet. Several expeditions of climbers have reached the Everest summit without using supplementary oxygen due to the acclimatization process that occurred during a month long ascent. World-renowned climbers Peter Habeler and Reinhold Messner were quoted as saying "Every 15 steps we collapsed into the snow to rest as we approached the summit - then we crawled on again." If you are thinking of shortcutting the acclimatization process taking a helicopter to the Everest summit, forget it. You would pass out immediately after leaving the pressurized cabin without oxygen support.